2016
DOI: 10.1177/1470320316670444
|View full text |Cite
|
Sign up to set email alerts
|

Volume regulatory hormones and plasma volume in pregnant women with sickle cell disorder

Abstract: Background:Sickle cell disease (haemoglobin SS (HbSS)) mainly affects those of West African origin and is associated with hypervolaemia. Plasma volume rises by up to 50% in normal pregnancy but was previously found to be paradoxically contracted in late sickle cell pregnancy. The renin–angiotensin–aldosterone system is activated very early in human pregnancy to support the plasma volume expansion. We hypothesised that activation of the renin–angiotensin–aldosterone system would be blunted in pregnant women wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 46 publications
1
8
0
Order By: Relevance
“…This pregnancy-related rise in GFR was small and not statistically significant in HbSS pregnancy, and was in fact less than 25% of the GFR increase in the HbAA pregnancy ( Table 2 ). The finding of significant blunting of the pregnancy-associated GFR increase in the pregnant HbSS, relative to HbAA pregnancy supports our previous finding of reduced PV expansion in pregnant HbSS women [ 13 ] since plasma volume and GFR tend to change in the same direction in pregnancy [ 22 ]. It also supports our hypothesis of a relative renal vasoconstriction and a reversal of the normal pregnancy vasodilatation in them.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…This pregnancy-related rise in GFR was small and not statistically significant in HbSS pregnancy, and was in fact less than 25% of the GFR increase in the HbAA pregnancy ( Table 2 ). The finding of significant blunting of the pregnancy-associated GFR increase in the pregnant HbSS, relative to HbAA pregnancy supports our previous finding of reduced PV expansion in pregnant HbSS women [ 13 ] since plasma volume and GFR tend to change in the same direction in pregnancy [ 22 ]. It also supports our hypothesis of a relative renal vasoconstriction and a reversal of the normal pregnancy vasodilatation in them.…”
Section: Discussionsupporting
confidence: 88%
“…It has been found to be reduced in preeclamptic pregnancies [ 21 , 22 ], but has not previously been examined in pregnant women with HbSS. In our previous study [ 13 ], we also found that non-pregnant HbSS women had a supranormal PV that did not change in pregnancy despite the blunted renin release, and postulated renal dysfunction to be a possible cause.…”
Section: Introductionmentioning
confidence: 74%
See 2 more Smart Citations
“…A pregnant woman is considered to be anaemic if her haemoglobin concentration during the first and third trimester of gestation is lower than 11.0g/dL or lower than 10.5g/dL in the second trimester of pregnancy [3]. The reason for these different values, in pregnancy, is that the plasma volume expansion of 40 to 50% exceeds the 20 to 25% increase in red cell mass leading to the physiological haemodilution [4,5]. This physiologic plasma expansion has been linked to favourable pregnancy outcome [6].…”
Section: Introductionmentioning
confidence: 99%